2023
DOI: 10.18596/jotcsa.1294230
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties, Photoluminescence, and Judd-Ofelt Parameters of Eu3+- Doped CoNb2O6 Phosphor

Abstract: Trivalent Eu-activated CoNb2O6 phosphors were fabricated using the molten salt method, which provides enhanced homogeneity and low sintering temperature. The ceramic samples were examined by spectral and structural analyses. In X-ray diffractions, the single phase of orthorhombic columbite type CoNb2O6 structure was obtained for 0.5-10 mol% Eu3+ doping concentrations, while a two theta peak shift towards the smaller angles occurred. SEM examinations show an irregular morphology and sub-micron grain sizes. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Also, as seen in SEM micrographs in Figure 4(a-e), increasing Eu 3+ concentration promotes the formation of collapses and holes in the grains. Moreover, it has been previously reported that the grain sizes of powder samples produced by the molten salt method at 800 °C are in the range of 0.05-2 m (20). However, in this study, boron was subsequently added and the temperature was increased to 900 °C after pelletization.…”
Section: Xrd and Sem-eds Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Also, as seen in SEM micrographs in Figure 4(a-e), increasing Eu 3+ concentration promotes the formation of collapses and holes in the grains. Moreover, it has been previously reported that the grain sizes of powder samples produced by the molten salt method at 800 °C are in the range of 0.05-2 m (20). However, in this study, boron was subsequently added and the temperature was increased to 900 °C after pelletization.…”
Section: Xrd and Sem-eds Resultsmentioning
confidence: 81%
“…The MNb2O6 structure has a significant advantage in that it can host guest ions with ionic sizes comparable to the Nb and divalent M 2+ ions found in the structure. As MNb2O6 structure, cobalt niobate (CoNb2O6) has been studied due to its magnetic (13)(14)(15)(16), neutron scattering (17), luminescence (18)(19)(20)(21), dielectric (22,23) gas sensing (24,25) and magnetic-thermodynamic (26,27) properties. Singh et al (22) reported the dielectric and ferroelectric properties of Ti 4+ doped CoNb2O6…”
Section: Introductionmentioning
confidence: 99%